PISA: the Pedagogical Price of an International Evaluation - Roberto Sanz Ponce; Ángela Serrano Sarmiento; Aurelio González Bertolín (Universidad Autónoma de Baja California, 2020)
This article aims to determine whether the "misuse" of PISA results has adverse impacts on the education system and its teachers. A hermeneutic methodology was employed, which consisted in a reflection on indicators identified from data analysis. The results observed included a continuous improvement among Spanish students in mathematics, science, and reading comprehension in different evaluations from 2006 to 2016, but the research also identified how the education system has changed and adapted based on the needs and requests of PISA, regardless of the needs of the students themselves. In conclusion, this study shows that PISAinforms education policy; the media and politicians distort the reality of results while targeting teachers; creativity, innovation, diversity, values education, and capacity building are being left behind; the school curriculum and schedules prioritize certain subjects; and equity is falling apart, leading to social divisions.